Brasileiros na Espanha: internet, migrações transnacionais e redes sociais - Barth, Daiani Ludmila (Universidade do Vale do Rio do Sinos, 2009)
This research approaches the uses of the Internet, especially MSN, Skype and Uol chat in the construction of experiences and maintenance of social networks of Brazilian migrants in Spain. The theoretical base encloses the social concepts of transnational migration, networks, uses and the Internet. The research is oriented in a qualitative perspective, centered in the ethnography (observation and interviews), considering, on the other hand, an experimentation of the online tools, mainly MSN Messenger, Skype, email, as methodological strategy of ethnographical approach of transnational migrations and, for another one, an empirical analysis of aspects of the interactions online and offline related to the social networks of Brazilian migrants in Spain. As results of these net interactions, the uses of the Internet are distinguished, for the Brazilian migrants, in the constitution of transnational familiar relations, in the update of contacts with the country of birth (Brazil), in the experience with not migrants
Keywords: etnografia na internet; redes sociais online e offline; migração transnacional; ethnography on the internet; social networks online and offline; transnational migration; Ciências Sociais Aplicadas